The Effect of Virtual Reallity-Based Intervention on Walking Ability in Children with Spastic Diplegic Cerebral Palsy : A Single-Subject Study - Riksma Nurahmi Rinalti Akhlan; Nita Nitiya Intan Tanbrin; Euis Heryati; Khimmataliev Dustnazar Omonovich (UNIK (Jurnal Ilmiah Pendidikan Luar Biasa), 2026)
Children with spastic diplegic cerebral palsy commonly experience limitations in walking ability, which significantly affect their functional independence and quality of life. This study aimed to examine the effect of a virtual reality–based intervention on walking ability in children with spastic diplegic cerebral palsy. A quantitative approach using a single-subject research design was employed. Three children participated as individual cases based on predefined inclusion criteria. The intervention was implemented across three phases: baseline-1, intervention, and baseline-2. Walking ability was assessed using performance tests and systematic observation, with outcomes measured using the Gross Motor Function Measure (GMFM). Data were analyzed through within-condition and between-condition analysis to identify changes across phases. The results demonstrated a consistent improvement in walking ability during the intervention phase, with increased stability and higher GMFM scores compared to baseline conditions. Improvements were maintained during the post-intervention phase, indicating a retention effect. These findings suggest that virtual reality–based intervention provides effective motor stimulation and supports improvements in walking ability in children with spastic diplegic cerebral palsy. Virtual reality may serve as a promising complementary approach in pediatric motor rehabilitation, particularly for enhancing motivation, engagement, and functional mobility.